ON VECTOR SUBBUNDLES OF THE VECTOR BUNDLES - Trenčevski, Kostadin (Matematichki Bilten, 1993)
In this paper are proved some theorems which give necessary and sufficient conditions for a real vector bundle of rank \(k\) to admit vector subbundle of rank \(m\) (\(m≤ k\)), or to admit \(m\) linearly independent vector fields. In the last section are considered complex vector bundles. Some ideas from the theory of complex commutative vector valued groups [2] are introduced in the complex vector bundles and two theorems are proved.